Penerapan Tema Green Architecture pada Agrowisata Kopi Arabika di Desa Belantih, Kintamani: Bahasa Indonesia - I Gede Soemantaranatha Eka Putra Wiratenaya; Agus Kurniawan; Ni Wayan Nurwarsih (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2023)
Agrotourism is a non-formal education effort for the local community as well as tourists who make tourist visits. Learning that takes place in agro-tourism is needed because it can support the learning process carried out in schools to deepen learning and have an impact on increasing academic understanding. Kintamani Arabica coffee in terms of quality and taste has been recognized by coffee connoisseur countries in the world. Belantih Village, which is in the Kintamani District, is one of the producers of Arabica coffee, in which every Banjar/Dusun has Subak Abian and farmer groups that regulate Arabica coffee farming activities, one of which is the Dharma Kria farmer group. The Dharma Kria farmer group is a farmer group in Banjar Luahan, Belantih Village which was formed in 2015 with 34 members. In the current era, in Bali coffee is increasingly being enjoyed by various groups. The increasing existence of coffee in Bali can be seen from the facilities of coffee shops in Bali, especially in the Kintamani District, which are increasing, however, there are still many who do not understand Kintamani Arabica coffee. Facilities that provide education and recreation that can be reached by various groups are urgently needed to accommodate tourists who want to learn more about the process of Kintamani Arabica coffee beans starting from the history of Kintamani Arabica coffee, planting, picking, processing, and serving Arabica coffee itself. Recreational activities can be carried out by spreading educational facilities at several points so that tourists feel the sensation of walking in the middle of the residents' coffee plantation area which has a cool climate. Data collection methods used include literature studies, field observations, and surveys